Development of a Microbial Fuel Cell Using Methylococcus Chroococcus Bacteria as a Biocatalyst - Hany S. Abdo (MDPI AG, 2021)
Methane is an extensively accessible green energy that can be obtained organically just by way of through natural gases. However, using methane in fuel at ambient temperature conditions is quite challenging, due to its high thermodynamically stability. In this present investigation, the feasibility of using methane in the low-temperature microbial fuel-cell (MFC) with an unadulterated culture of Methylococcus chroococcus without the inclusion of any additional electron mediators is investigated. The microbial fuel cell setup was prepared using a salt bridge. Through potentiodynamic study, power density, and OCV, it can be seen that the setup delivers a sufficient amount of voltage and power as the days progress. Electrochemical Impedance Spectroscopic investigations also depict the fact that the cell required roughly one day to balance out, and kept working at full force for up to seven days. This work exhibits the chance of creating power utilizing methane as one of the main carbon sources at ambient temperature with an M. chroococcus unadulterated culture as the direct electron-transporting MFC biocatalyst.